Genetic and physiological requirements for high-level sesquiterpene-production in tomato glandular trichomes - Kortbeek, Ruy W. J.; Galland, Marc D.; Muras, Aleksandra; Therezan, Rodrigo; Maia, Sofia; Haring, Michel A.; Schuurink, Robert C.; Bleeker, Petra M. (Frontiers in Plant Science, 2023)
Type-VI glandular trichomes of wild tomato Solanum habrochaites PI127826 produce high levels of the sesquiterpene 7-epizingiberene and its derivatives, making the plant repellent and toxic to several pest insects and pathogens. How wild tomato trichomes achieve such high terpene production is still largely unknown. Here we show that a cross (F1) with a cultivated tomato produced only minute levels of 7-epizingiberene. In the F2-progeny, selected for the presence of the 7-epizingiberene biosynthesis genes, only three percent produced comparable amounts the wild parent, indicating this trait is recessive and multigenic. Moreover, trichome density alone did not explain the total levels of terpene levels found on the leaves. We selected F2 plants with the “high-production active-trichome phenotype” of PI127826, having trichomes producing about 150 times higher levels of terpenes than F2 individuals that displayed a “low-production lazy-trichome phenotype”. Terpene quantities in trichomes of these F2 plants correlated with the volume of the storage cavity and shape of the gland. We found that trichome morphology is not a predetermined characteristic, but cavity volume rather depended on gland-cell metabolic activity. Inhibitor assays showed that the plastidial-precursor pathway (MEP) is fundamental for high-level production of both cytosolic as well as plastid-derived terpenes in tomato trichomes. Additionally, gene expression profiles of isolated secretory cells showed that key enzymes in the MEP pathway were higher expressed in active trichomes. We conclude that the MEP pathway is the primary precursor-supply route in wild tomato type-VI trichomes and that the high-production phenotype of the wild tomato trichome is indeed a multigenic trait.